Comparative genomic, transcriptomic and phenomic analyses on quorum sensing of Hafnia alvei / Tan Jia Yi - Tan , Jia Yi (2019)
Quorum sensing (QS) is the regulatory event achievable via cell-to-cell communication that involves release and detection of autoinducers (AIs), which occurs in a wide range of bacteria. To date, QS has been associated to events of pathogenesis, biofilm formation, antibiotic resistance in clinical, industrial, as well as agricultural aspects. The focus of this study lies on the acyl-homoserine lactone (AHL) type QS in Hafnia alvei, an opportunistic pathogen and potential spoilage agent. H. alvei FB1 was obtained in an attempt to isolate AHL-producing strains from “fish ball”, a popular street food made of fish paste. The main objective of this study is to investigate the role of AHL type QS in FB1 via identification of QS core genes using genomic approach, followed by transcriptomic and phenomic comparative profiling between QS-deficient mutants and the wildtype strains. In this study, H. alvei FB1 has been found to produce two types of AHLs, namely, N-(3-oxohexanoyl) homoserine lactone (3OC6-HSL) and N-(3- oxooctanoyl) homoserine lactone (3OC8-HSL). Complete genome sequence of FB1 was obtained and a single pair of AHL synthase (halI) and its cognate receptor (halR) genes were identified. QS-deficient mutants of FB1 were constructed via λ-Red recombineering method. Comparative study showed that the removal of QS genes in FB1 affected mainly mechanisms in cell division, nutrient uptake, as well as resistance to a number of antibiotics, which were crucial for survival, adaptation and colonisation of the organism in both food and host gut environment. In conclusion, this study has served its role as a preliminary fundamental study with the hope to pave the advancement of more in depth study and application in future.